Self-selected resistance training intensity in novice weightlifters - Glass, S. C.; Stanton, D. R. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this study was to determine the intensity of self-selected weightlifting exercise in untrained men and women. Thirteen men (age = 19.5 ± 1.9, height = 70.0 ± 2.4 in., weight = 174 ± 20.1 lb, % fat = 14.3 ± 6.7) and 17 women (age =18.7± 1.0, height = 64.9 ± 2.3 in., weight = 135.4 ± 22.8 lb, % fat= 23.4 ± 4.7) who were novice lifters completed seated bench press, leg extension, seated back row, military press, and biceps curl. Following self-selection trials, subjects' 1 repetition maximum (1RM) was assessed for each lift. Results showed that for both genders, self-selected loads were all below 60% 1RM. All lift intensities were similar for men and women (range = 42-57% 1RM). Repetitions completed and rating of perceived exertion responses were not different between gender. Results show that subjects do not select a lifting intensity sufficient to induce hypertrophic responses and subsequent strength increases.